Plant life history strategies vary in subtropical forests with different disturbance histories: an assessment of biodiversity, biomass, and functional traits - Liu, Julian; Xia, Haojun; Zheng, Zihong; Wang, Yunquan; Chen, Jianhua; Ni, Jian; Yu, Mingjian; Zheng, Weicheng; Liu, Libin (Frontiers in Plant Science, 2024)
Disturbance alters environmental conditions in forests. Plants growing in forests with different disturbance histories in diverse environments may adopt varying life history strategies, but few studies focus on this effect. This study comprehensively investigated plant biodiversity, biomass, and functional traits in subtropical forests with two different disturbance histories in east China to explore differences in life history strategies. Biodiversity was slightly higher in disturbed compared to conserved forests. Significantly higher biomass was measured in conserved relative to disturbed evergreen broadleaved forests (P < 0.05). In conserved forests, leaf tissue density (LTD) was significantly higher and leaf thickness (LT), leaf dry matter content (LDMC), twig tissue density (TTD), twig dry matter content (TDMC), bark tissue density (BTD) and dry matter content (BDMC), and stem tissue density (STD) and dry matter content (SDMC) were significantly lower than in disturbed forests (P < 0.05). In terms of associated plant biodiversity, biomass, and functional traits, conserved forests adopted a resource acquisition strategy, reducing biodiversity and developing multiple functional traits such as high leaf area and specific leaf area and low LT, LDMC, TTD, TDMC, BTD, BDMC, STD, and SDMC to support a high biomass accumulation rate. Disturbed forests adopted a resource conservation strategy, enhancing biodiversity and developing converse trait combinations to lower the rate of biomass accumulation. A comprehensive investigation of plant biodiversity, biomass, and functional traits and subsequent assessment of plant life history strategies in conserved and disturbed forests will aid investigations of regional biodiversity and carbon reserves, Life history strategies of disturbed forests 2 contribute data to the TRY and Chinese plant trait databases, and improve ecological management and restoration efforts in east China.